Answer:
x=4
Explanation:
1) Distribute x through the parenthesis: (6x-2x^2)*(3-2x)=40
2) Multiply the parentheses: 18x-12x^2-6x^2+4x^3=40
3) Collect the like terms: 18x-18x^2+4x^3=40
4) Divide the both sides of the equation by 2: 9x-9x^2+2x^3=20
5) Move the constant to the left and change its sign: 9x-9x^2+2x^3-20=0
6) Use the commutative property to reorder the terms: 2x^3-9x^2+9x-20=0
7) Write -9x^2 as a difference: 2x^3-8x^2-x^2+9x-20=0
8) Write 9x as a sum: 2x^3-8x^2-x^2+4x+5x-20=0
9) Factor out 2x^2 from the expression: 2x^2(x-4)-x^2+4x+5x-20=0
10) Factor out -x from the expresstion: 2x^2(x-4)-x(x-4)+5x-20=0
11) Factor out 5 from the expression: 2x^2(x-4)-x(x-4)+5(x-4)=0
12) Factor out x-4 from the expression: (x-4)(2x^2-x+5)=0
13) When the product of factors equals 0, at least one factor is 0:
x-4=0
2x^2-x+5=0
14) Solve the equation for x:
x=4
x≠R
15) Find the union: x=4